PERANCANGAN GAME BERJENIS THIRD PERSON DENGAN TEMA PEMADAM KEBAKARAN PLATFORM ANDROID - Joshua Roniek (Universitas Mercu Buana, 2019)
Game is one of the entertainment because it can reduce the level of fatigue of daily work routines. This game is also able to increase one's intelligence when playing. The purpose of this research is to design a game application that is used as a medium of entertainment and also a fire extinguisher simulation for people in need.In this study using the interview method and see the simulation that was carried out during fire fighting training organized by PT Gajah Tunggal TBK. The making of this game application uses the Unity 4 series game engine supported by the Asset store unity package which makes it easy to make this game a Blackbox and Whitebox method in testing so that all scripts can run as they should so that no errors occur when the application is run.This research resulted in the application of the Third Person Type Game with a Fire Extinguisher Theme, which has difficulties at each level that have been set according to circumstances that are almost similar to the actual events so that users become challenged in playing the third-person game-themed extinguisher.